Patterns of Larval Emergence and Their Potential Impact on Stock Differentiation in Beach Spawning Capelin ( Mallotus villosus ) - Fortier, Louis; Leggett, William C.; Gosselin, Serge (Canadian Journal of Fisheries and Aquatic Sciences, 1987)
The environmental cues triggering larval capelin (Mallotus villosus) emergence in the St. Lawrence estuary and in coastal Newfoundland are different. In the estuary, emergence from the intertidal and subtidal spawning grounds starts with dusk and ends with dawn, indicating an active response to low light intensity. In the laboratory, emergence from undisturbed sediments collected in the field is perfectly synchronized with the dark phase of the illumination cycle. Nocturnal emergence would represent an adaptation reducing vulnerability to visual predators. Previous work has shown that in Newfoundland, capelin emergence from intertidal beaches is triggered by abrupt changes in water temperature following the sporadic advection to the coast of surface water masses characterized by low predator and high prey abundances. We argue that regional differences in the emergence pattern of the species represent different strategies to avoid predation at the onset of the planktonic drift when the vulnerable yolk sac larvae are densely aggregated. Selection acting on the behaviour of the early larval stages could contribute to stock differentiation in capelin.